Financial risk system dynamics modeling for investment decision in solar thermal technologies for Malaysia's industries / Anis Sabirin Baharom and Nofri Yenita Dahlan - Baharom, Anis Sabirin; Dahlan, Nofri Yenita (UiTM Press, 2018)
The objective of this study is to analyze the impact of financial risk as part of the investment risk for solar thermal heating installation in Malaysia. The solar thermal installation is focusing on small medium enterprises (SME) industries. In this work, the Net Present Value (NPV) of the projects is investigated over existing condition where no specific policy and financial mechanism available for solar thermal heating installation in Malaysia as a base case, and with various government's supports as case studies. The financial risk is measured through a model developed using System Dynamics simulation technique. Monte Carlo simulation using Excel software is used for solar thermal heating energy demand by Malaysian industries for the next 20 years. Meanwhile, Monte Carlo simulation technique by Vensim software is used for the financial risk behavior validation. The results reveal that the government support and financial funding mechanism has great influence on the investment decision which lead to the increase of solar thermal install capacity by Malaysian SME industries. The policy maker can benefit from the result obtained in tailoring the better policy for solar thermal heating in SME industries.